Governança corporativa: os investidores institucionais realmente importam no mercado acionário brasileiro? - Scaramussa, Filipe Manarte (2022)
This study observed the existence of a relationship between the presence of different types of institutional investors in the shareholding structure of Brazilian companies and their corporate governance practices. The study analyzed a sample composed of 118 companies over the period between 2010 and 2020, totaling 1298 company-year observations. An index consisting of 20 objective questions, the IPGC, was used to measure corporate governance practices adopted by companies. The number of institutional investors present in the shareholding structure of companies was observed, a factor not yet explored by the national literature as an explanatory variable for corporate governance practices. The study also classified institutional investors present among the five largest shareholders of the companies in the sample in each year analyzed in Pension Funds, Investment Funds and Funds Managed by Financial Institution, also observing whether the institution is of foreign or national origin and of a private or state. For econometric analysis, descriptive statistics, Pearson's correlation matrix, and regression models were used, with special emphasis on the use of GMM-Sys in a robust and detailed manner. The results show that the number of institutional investors in the company's shareholding structure, the participation of Pension Funds, and the participation of Foreign Investment Funds are positively related to the IPGC, suggesting that these institutions are more effective in monitoring the investees and seek to influence them in the search for improvements in their corporate governance practices. In turn, the presence of Funds Managed by Financial Institutions showed a negative relationship with the IPGC, while the state nature of some institutional investors did not show statistical significance in relation to the IPGC. By indicating the relationship between different types of institutional investors and the corporate governance practices of the investees, this study contributes to a better perception of risk by investors and other participants in the Brazilian stock market, as well as to the advancement of the literature on the subject.